Comparative Transcriptome Reveals the Genes’ Adaption to Herkogamy of Lumnitzera littorea (Jack) Voigt - Zhang, Ying; Chen, Yukai; Zhou, Yan; Zhang, Jingwen; Bai, He; Zheng, Chunfang (Frontiers in Genetics, 2020)
Lumnitzera littorea (Jack) Voigt is among the most endangered mangrove species in China. The morphology and evolution of L. littorea flowers have received substantial attention for their crucial reproductive functions. However, little is known about the genomic regulation of flower development in L. littorea. In this study, we characterized the morphology of two kinds of L. littorea flowers and performed comparative analyses of transcriptome profiles of the two different flowers. Morphological observation showed that some flowers have a column embedded in the petals while others produce a stretched flower style during petal unfolding in flowering. By using RNA-seq, we obtained 138,857 transcripts that were assembled into 82,833 unigenes with a mean length of 1055.48 bp. 82,834 and 34,997 unigenes were assigned to 52 gene ontology (GO) functional groups and 364 Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, respectively. A total of 4,267 differentially expressed genes (DEGs), including 1,794 transcription factors (TFs), were identified between two types of flowers. These TFs are mainly involved in bHLH, B3, bZIP, MYB-related, and NAC family members. We further validated that 12 MADS-box genes, including 4 MIKC-type and 8 M-type TFs, were associated with the pollinate of L. littorea by herkogamy. Our current results provide valuable information for genetic analysis of L. littorea flowering and may be useful for illuminating its adaptive evolutionary mechanisms.